High performance programme - policy document (2003)
The purpose of this document is to outline the policy guidelines for all the role-players participating in the HPP. Through this policy document the SASC intends to provide more clarity and direction regarding its scientific and medical support services to elite athletes. The recommendations made at the HPP evaluation workshop held on 4 & 5 March 2003 were considered when revising these guidelines. Inputs were also received from the SASC High Performance Committee and the Sports Science and Medical Committee.